A new method to assess passive and active ankle stiffness during quiet upright stance. Issue 6 (December 2015) - Zhang, Hongbo; Nussbaum, Maury A.; Agnew, Michael J.
Abstract: Both passive and active ankle torque contribute to postural stability during quiet upright stance, yet directly measuring their relative contributions is difficult. Here, a new method was developed to estimate passive and active ankle stiffness (ST) and damping (DA). In contrast to earlier approaches, the proposed method does not require external mechanical or sensory perturbations. Instead, the method is based on the assumption that upright stance is intermittently controlled, and that active ankle torque is in-phase coherent with ankle angular acceleration. Thus, identifying the local maxima of ankle angular accelerations facilitates the identification of time windows that include substantial active ankle torque. After identifying these local maxima and associated windows, estimates of passive and active ankle ST and DA were obtained using linear regression analyses. Consistent with earlier work, passive ankle torque was estimated to account for 94–97% of the total ankle torque, and to have linear relationships with ankle angle and angular velocity. Predicted values of passive and active ankle stiffness were also consistent with earlier reports. This new approach may be a useful tool to efficiently investigate passive and active joint stiffness during quiet upright stance.